One gene to rule them all – clinical perspectives of a potent suppressor of cytokine signaling – SOCS1 - Körholz, Julia; Chen, Lan-Sun; Strauss, Timmy; Schuetz, Catharina; Dalpke, Alexander H. (Frontiers in Immunology, 2024)
The discovery of Suppressor of Cytokine Signaling 1 (SOCS1) in 1997 marked a significant milestone in understanding the regulation of Janus kinase/Signal transducer and activator of transcription (JAK/STAT) signaling pathways. Subsequent research deciphered its cellular functions, and recent insights into SOCS1 deficiencies in humans underscored its critical role in immune regulation. In humans, SOCS-haploinsufficiency (SOCS1-HI) presents a diverse clinical spectrum, encompassing autoimmune diseases, infection susceptibility, and cancer. Variability in disease manifestation, even within families sharing the same genetic variant, raises questions about clinical penetrance and the need for individualized treatments. Current therapeutic strategies include JAK inhibition, with promising results in controlling inflammation in SOCS1-HI patients. Hematopoietic stem cell transplantation and gene therapy emerge as promising avenues for curative treatments. The evolving landscape of SOCS1 research, emphasizes the need for a nuanced understanding of genetic variants and their functional consequences.